2019
DOI: 10.1039/c9ra02942g
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between crystalline disorder and electronic structure of Pd nanoparticles and their hydrogen storage properties

Abstract: Smaller Pd nanoparticles have a high degree of disordering and a lower coordination number on the surface part, which causes a change in electronic structure to have different hydrogen storage properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Hydrogen gas sensors that use various sensing materials have been widely studied by many research groups for over two decades [ 5 , 6 , 7 , 8 ]. Recently, palladium nanomaterial-based sensors that can detect down to ppm level at room temperature have been developed [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen gas sensors that use various sensing materials have been widely studied by many research groups for over two decades [ 5 , 6 , 7 , 8 ]. Recently, palladium nanomaterial-based sensors that can detect down to ppm level at room temperature have been developed [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…From a different point of view, almost the constant value for DWF by hydrogenation indicates that small NPs have a distortion in the inside of metal NP. 10,25 Hydrogen absorption reaction can release the distortion of Rh NP.…”
Section: Resultsmentioning
confidence: 99%
“…Seo et al reported that the lattice's structural order was improved with particle diameters increasing from 2.0 nm to 7.6 nm Pd NPs. 19) Ulvestad et al examined an initial stage of hydride formation (to PdH 0.05 ) using X-ray diffraction on a small Pd cubic crystal. 20) They observed that a hydrogen-rich surface layer dominated the crystal strain in the hydrogenpoor phase.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of size plays a critical role in the hydrogen storage behavior of NPs and several models were discussed in detail, in terms of the coexisting surface and bulk and the interfacial and domain configurations of particles from as small as several nm up to a few hundred nm in diameter. [10][11][12][13][14][15][16][17][18][19][20][21][22] Many researchers have applied different fabrication methods and their NPs did not all have the same features such as as shape, size distribution and crytallinity, because the control of a series of NP sizes is generally difficult when using the same process. In addition, typical micrographic images are often provided in references, however, generally speaking, not all samples have the same status.…”
Section: Introductionmentioning
confidence: 99%